COMPARATIVE STUDY OF HEMODYNAMIC RESPONSE USING LARYNGEAL MASK AIRWAY (LMA) VERSUS ENDOTRACHEAL TUBE (ETT) IN CONTROLLED HYPERTENSION PATIENTS - ABIDIN, ZU; WADOOD, R; AHMED , N; ABBASI, T; ULLAH, A; KHAN, IU (Biological and Clinical Sciences Research Journal, 2023)
In the practical conduct of Anaesthesia, Airway management is crucial to the outcome & best patient care. A total of n=114 patients,30-50 yrs with mean age 38.736± 4.36 years; 57 each group of Laryngoscopy and ETT; and LMA group undergoing elective surgery of 30 minutes to 01-hour duration in controlled hypertensives were included in the study. The hemodynamic response was noted, recording pulse rate, Systolic BP, Diastolic BP, and MAP immediately after 1,3,5 minute of laryngoscopy & intubation or LMA insertion. The study results showed a hemodynamic response of 59.6% in patients of the Laryngoscopy & ETT group compared to 40.4% in the LMA group. The study revealed attenuated hemodynamic response to LMA insertion with improved hemodynamic; stability compared to laryngoscopy & intubation. The results advocate using supraglottic airway devices, especially LMA merits, in selected patients & circumstances.